HUMORICAL ADVERTISING AS A FRAGMENT OF A MEDIA-ADVERTISING PICTURE OF THE WORLD (ON THE PLAN OF RUSSIAN AND SERBIAN LANGUAGES) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
The article examines the characteristics of Russian and Serbian humorous advertising in the light of the general media advertising and linguistic picture of the world as one of the features of modern research in linguistics, journalism, and media theory. The phenomenon is observed from the point of view of the influence of the advertising language on the consciousness and everyday life of modern consumers. The language of advertising reflects modern phenomena in the social and cultural life of society, and also creates a new meaning that determines the behavior of most people. Thus, advertising as a more aspectual phenomenon attracts the attention of researchers in various fields of science, including linguistics, journalism, sociology, and psychology. The subject of our research is contemporary Russian and Serbian humorous advertisements available on Russian and Serbian TV programs, the Internet and state media.
Keywords: humorous advertisment; linguistic interpretation; media interpretation; Russian humorous advertisment; Serbian humorous advertisment